Enhancing Student Interactivity And Creativity Through PAIKEM On Learning Islamic Education In The Digital Age - Diplan; Rini; Ningsih, Salsabila Hady (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2025)
This study discusses applying the PAIKEM method (Active, Innovative, Creative, Effective, and Fun) in learning in the digital era. This study aims to determine how PAIKEM can increase student enthusiasm in learning and make the learning process more interesting and meaningful. This study uses a literature review method, reviewing various sources such as books and scientific articles. The study results indicate that using technology in PAIKEM can help students become more active, creative, and better understand the subject matter. However, challenges include limited technological facilities and teachers' ability to use digital learning media. Therefore, teacher training and creativity enhancement must ensure that PAIKEM can optimally implement in the digital era. Proper implementation will make learning more enjoyable, and learning objectives can be achieved more effectively. This study can serve as a reference for improving student interaction and creativity in Islamic education teaching by the terms inherent in the acronym PAIKEM.